2021
DOI: 10.1177/2333794x21996630
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Dietary Diversity Practice and Associated Factors among Children Aged 6 to 23 Months in Dire Dawa City, Eastern Ethiopia: A Community-Based Cross-Sectional Study

Abstract: Objective: Malnutrition because of poor dietary diversity contributing to child morbidity and mortality. Two-thirds of child mortality occurs within the first 2 years. However, there is limited data related to dietary diversity among children aged 6 to 23 months in Ethiopia. Thus, this study aimed to assess dietary diversity and factors among children aged 6 to 23 months in the study setting. Methods: A community-based cross-sectional study conducted on 438 children aged 6 to 23 months in Dire Dawa, 1-30/02/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
2
14
1
Order By: Relevance
“…This finding is higher than a study conducted in Bangladesh that stated 60% of children consumed dietarily diversified food ( 28 ). This result was also higher than a study conducted in Ethiopia, which found 24.4% of children had minimum DD ( 40 ). A possible reason is that, during the COVID-19 pandemic, mothers and fathers stayed at home, prepared food, and fed diversified food to their children.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding is higher than a study conducted in Bangladesh that stated 60% of children consumed dietarily diversified food ( 28 ). This result was also higher than a study conducted in Ethiopia, which found 24.4% of children had minimum DD ( 40 ). A possible reason is that, during the COVID-19 pandemic, mothers and fathers stayed at home, prepared food, and fed diversified food to their children.…”
Section: Discussioncontrasting
confidence: 71%
“…68.23 % of the population was urban residents. Dire Dawa administration has 2 Hospitals and 8 Urban Health Centers [30]. All the health centers provide ANC service.…”
Section: Study Areamentioning
confidence: 99%
“…The overall results regarding the dietary diversity score of preschool children showed that most preschool children didn't achieve a minimum dietary diversity score. However, less than a quarter of preschool children met the minimum dietary diversity score requirements in the last 24 h. The result found was lower than the study conducted in the Diredawa city, Ethiopia (24.4%) [33] and Tanzania (38%) [11]. However, the obtained result was higher when compared to the Ethiopia Demographic & Health Survey [26], in which 5% of children had minimum dietary diversity [26].…”
Section: Discussionmentioning
confidence: 70%
“…Of those, 66% of deaths were due to poor feeding practices during the first 2 years of life [8,9]. In developing countries, inappropriate dietary diversity is the major reason for childhood malnutrition which is strongly associated with morbidity and mortality [10,11].…”
Section: Introductionmentioning
confidence: 99%